2022
DOI: 10.3389/fimmu.2021.817893
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Therapy After Autologous Hematopoietic Stem Cell Transplantation in Systemic Sclerosis Patients—High Efficacy of Rituximab

Abstract: BackgroundSystemic sclerosis (SSc) patients often need immunosuppressive medication (IS) for disease control. If SSc is progressive despite IS, autologous hematopoietic stem cell transplantation (aHSCT) is a treatment option for selected SSc patients. aHSCT is effective with good available evidence, but not all patients achieve a treatment-free remission after aHSCT. Thus far, data about the need of IS after aHSCT in SSc is not published. The aim of this study was to investigate the use of IS after aHSCT, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…In fact, longer-term follow-up of pulmonary function and alterations shows that the effects of AHSCT on the evolution of ILD tend to decrease over-time and eventually disappear in some patients, returning to the pre-transplant conditions two years after AHSCT. For this group of patients, Rituximab, an anti-cd20 biologic agent, showed a promising profile of safety and efficacy, offering the opportunity to avoid ILD recurrence or worsening after AHSCT [ 45 ]. This directly raises the question whether future trials should focus on the stabilization of pulmonary function improvement after AHSCT and to identify SSc patients at risk of long-term ILD progression or re-activation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, longer-term follow-up of pulmonary function and alterations shows that the effects of AHSCT on the evolution of ILD tend to decrease over-time and eventually disappear in some patients, returning to the pre-transplant conditions two years after AHSCT. For this group of patients, Rituximab, an anti-cd20 biologic agent, showed a promising profile of safety and efficacy, offering the opportunity to avoid ILD recurrence or worsening after AHSCT [ 45 ]. This directly raises the question whether future trials should focus on the stabilization of pulmonary function improvement after AHSCT and to identify SSc patients at risk of long-term ILD progression or re-activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, targeted B-cell therapy with rituximab might be considered. Rituximab represents a promising strategy for skin and lung fibrosis in SSc but long term data is missing and in fact, to date, this is an experimental treatment also ( 11 , 14 , 16 ). Furthermore, treatment with Nintedanib was discussed but declined as this has not shown effect on skin involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Findings that suggest this include changes to in vitro IL-10 production with CpG-stimulated purified patient total B cells [ 59 ] and by inhibition of IFNg and TNFa production with in vitro stimulated CD4 T cells [ 58 ]. However, if Bregs play a significant role, it is difficult to explain why rituximab appears effective in patients who relapsed after HCT [ 60 , 61 ], with rituximab theoretically expected to eliminate the few Bregs that the relapsing patients may still possess. One such explanation could be that rituximab does not in practice deplete all B cell populations, as has been seen with marginal zone B cells [ 62 ].…”
Section: Proposed Mechanisms Of Action Of Autohct On Sscmentioning
confidence: 99%
“…For example, in the SCOT trial, 9% of HCT recipients vs. 44% of controls started an immunomodulatory drug within the first 4.5 years [ 23 ], with the difference remaining significant at 6–11 years [ 95 ]. Aside from the randomized trials, disease progression varies among longitudinal studies but has been reported to occur in 11% to almost 31% [ 44 , 45 , 60 , 145 ] of patients at 4.4 years, 10.5% to 24% at 8 years [ 107 , 117 ], and 42% at 11 years [ 75 ] after HCT. While the reasons for this heterogeneity are unclear, it is likely due to differences in patient selection, follow-up duration, and the definition of relapse used.…”
Section: Relapse/ssc Progressionmentioning
confidence: 99%
See 1 more Smart Citation